Struktur dan Komposisi Vegetasi Mangrove di Desa Lalombi Kecamatan Banawa Selatan Kabupaten Donggala - Endang P. Wahyuningsih; Samsurizal M. Suleman; Ramadhanil Ramadhanil (Biocelebes, 2012)
The research on the structure and composition of mangrove vegetation in the Lalombi Village South Banawa Donggala District has been conducted from November to December 2012 which aims to determine the structure and composition of mangrove vegetation in the studied area. The research was used exploratory survey method by using line (transect method) and in the transects, plots were made in the size 10 m X 10 m for the observation of trees, 5 m X 5 m for the poles and the 2 m X 2 m for seedlings. The result of the research showed that there were 11 species of mangrove namely : Ceriops tagal, Ceriops decandra, Aegiceras corniculatum, Avicennia marina, Sonneratia alba, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorhiza, Camptostemon philipinense, Xylocarpus molluccensis and Bruguiera parviflora. It’s belong to 6 family that Rhizophoraceae, Myrsinaceae, Avicenniaceae, Sonneratiaceae, Meliaceae and Bombacaceae. The diversity index of Mangrove species at Lalombi village was low. Species Mangrove of trees in the studied area were dominated by Sonneratia alba (INP 82.41%), meanwhile Aegiceras corniculatum (INP 69.71%) and Ceriops tagal were dominant on the level of sapling and seedling (62.21%). Key words: Structure, composition, mangrove, Lalombi village